EKSPLORASI KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK PADA PEMBELAJARAN PROBLEM BASED LEARNING - Fitria Adri Dwi Anisah; Sri Yunita Ningsih (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
This study investigates the mathematical communication competencies of students engaging in Problem Based Learning (PBL) within a classroom setting. A qualitative descriptive design was employed, with the study conducted at SMP Negeri 2 Lirik. Six participants were selected, representing three proficiency categories: high, intermediate, and low. Data were gathered through classroom observation, written assessments, and structured interviews. Results revealed that high-ability students articulated mathematical reasoning coherently and applied symbolic notation accurately. Intermediate-ability students were capable of completing tasks but provided incomplete justifications, while low-ability students faced considerable challenges in expressing mathematical concepts verbally and in writing. Overall, the PBL environment fostered greater student participation in collaborative discussion and facilitated the development of mathematical communication skills.Keywords: Problem Based Learning, mathematical communication, mathematics education